Tourism Suitability Index at Mengening Beach, Badung Regency, Bali - I Gusti Ngurah Putra Dirgayusa; I Gede Surya Indrawan; Br Sitepu, Fany Ekaristy (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
The Tourism Suitability Index (IKW) shows the assessment of an area regarding the level of suitability/feasibility to become a tourist attraction. An important aspect in the use of natural resources for tourism activities is the suitability of tourism and strategies for its development. The research aims to determine the value of the Tourism Suitability Index (IKW) and development strategies that can be used for management at Mengening Beach, Badung Regency, Bali. Data collection was carried out in April-May 2024 at three observation stations. Data collection uses primary and secondary data. Primary data is based on observations of beach type parameters, beach width, depth, beach slope, current speed, water brightness, bottom water material, land cover, availability of clean water, dangerous biota as well as questionnaire interviews with beach visitors using purposive sampling techniques. Data analysis uses the results of IKW measurements and SWOT analysis. Based on IKW calculations at three points, namely station I of 2,195, station II of 2,475, and station III of 2,475. The total analysis value of 2.0 ≤ IKW < 2.5 is included in the appropriate category. The strategy that can be applied at Mengening Beach in developing beach tourism is the SO (Strength-Opportunity) strategy, which involves external management at Mengening Beach, optimizing the use of social media and adding tourist attractions at Mengening Beach.